N‐Fluoroalkylated Morpholinos – a New Class of Nucleoside Analogues. Issue 11 (12th January 2023) - Debreczeni, Nóra; Hotzi, Judit; Bege, Miklós; Lovas, Miklós; Mező, Erika; Bereczki, Ilona; Herczegh, Pál; Kiss, Loránd; Borbás, Anikó
Abstract: The first concise and efficient synthesis of some fluorine‐containing morpholino nucleosides has been developed. One synthetic strategy was based on the oxidative ring cleavage of the vicinal diol unit of uridine, cytidine adenosine and guanosine derivatives, followed by cyclisation of the dialdehyde intermediates by double reductive amination with fluorinated primary amines to obtain various N ‐fluoroalkylated morpholinos. Another approach involved cyclisation of the diformyl intermediates with ammonia source, followed by dithiocarbamate formation and desulfurization‐fluorination with diethylaminosulfur trifluoride yielding the corresponding morpholine‐based nucleoside analogues with a N ‐CF3 element in their structure. Abstract : The first synthesis of N ‐fluoroalkylated morpholino nucleoside derivatives is reported. The procedures were based either on a double reductive amination‐cyclisation reaction, using commercially available mono‐, di‐ and trifluoralkylated amines, or on post‐cyclisation trifluoromethylation of the morpholino nitrogen, by oxidative desulfurization‐fluorination with NBS and diethylaminosulfur trifluoride.